Peningkatan Kualitas SDM dan Daya Dorong Ekonomi BUMDes Sirnajaya Garut - Yunita Christy; Joni; Rini Handayani; Sinta Setiana; Maria Natalia; Imelda Lisa; Sherin Ivana Dewi (SULUH: Jurnal Abdimas, 2020)
This community service aims to overcome one of the problems of the Village Owned Enterprises (BUMDes) in Sirnajaya Village, Tarogong Kaler District, Garut Regency, West Java. The problem is that the quality of human resources is low in motivation and competence so that many of the businesses that are run do not operate well, one of which is the business of selling gasoline through mini gas stations. Efforts have been made to improve the operation of the mini gas station business by providing training to improve the quality of human resources in terms of financial literacy and increasing economic impetus in Sirnajaya Village. The training was given to several BUMDes management and meru is a collaboration with the Indonesian Smart Bear Foundation.